A unified normalization framework for dissipated energy in anisotropic aortic tissue under biaxial stretching - Cai, Renye; Liu, Jinchuan; Cai, Jinfeng; Zhang, Heng; Bo, Tianyu; Chen, Ri; Liu, Jian; Yang, Guanda; Qu, Muchao (APL Materials, 2025)
This study investigates the anisotropic mechanical properties and energy dissipation behavior of aortic tissue under biaxial stretching. By introducing the reciprocal value of the self-stretching ratio and the standardization factor, we established a unified framework linking strain-dependent Young’s modulus to energy dissipation in the radial and axial directions. The results suggest different mechanical roles of collagen and elastic fibers in maintaining structural integrity and adaptability under physiological conditions. A novel normalization process was developed to eliminate the influence of modulus variation, enabling precise evaluation of energy dissipation. These findings provide valuable insights into vascular biomechanics and contribute to the understanding of diseases such as atherosclerosis and aneurysms.
CRIS-Team Scopus Importer:2025-12-26